Polyarylene sulfide resin composition and molded article composed of the same

JP2025036005APending Publication Date: 2025-03-14TEIJIN LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024005960
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-29
Filing Date
2024-01-18
Publication Date
2025-03-14

AI Technical Summary

Benefits of technology

【0009】 本発明の樹脂組成物は押出性、薄肉成形性および電磁波シールド特性に優れるため、本発明の樹脂組成物より得られる成形品は電気·電子機器部品および自動車部品等の電磁波シールド性が必要とされるパーツに有用であり、その奏する工業的効果は極めて大である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025036005000003
    Figure 2025036005000003
  • Figure 2025036005000004
    Figure 2025036005000004
  • Figure 2025036005000005
    Figure 2025036005000005
Patent Text Reader

Abstract

To provide a resin composition which is excellent in extrudability, thin wall moldability, and electromagnetic wave shielding characteristics.SOLUTION: A resin composition contains, with respect to 100 pts.wt. of a component composed of 60 to 99.9 pts.wt. of (A) a polyarylene sulfide resin (component A), and 0.1 to 40 pts.wt. of (B) at least one resin (component B) selected from the group consisting of a polyamide resin and a polyester resin, 5 to 50 pts.wt. of (C) a metal-coated carbon fiber (component C), wherein when the resin composition is observed by a scanning electron microscope, a resin A of the component A forms a matrix, and the periphery of the metal-coated carbon fiber C of the component C is coated with a resin B of the component B.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition comprising at least one resin selected from the group consisting of polyarylene sulfide resins, polyamide resins, and polyester resins, and metal-coated carbon fibers, the resin composition having excellent extrudability, thin-wall moldability, and electromagnetic wave shielding properties. [Background technology]

[0002] Many devices now communicate wirelessly, such as Wi-Fi and Bluetooth, and electromagnetic waves are flying around in offices and homes filled with electronic devices and electrical appliances. In the future, with the spread of robots and drones that require remote control, it is expected that electromagnetic compatibility (EMC measures), which allows necessary electromagnetic waves to be accepted and shields unnecessary electromagnetic waves, will become increasingly important. Electronic devices that require electromagnetic shielding are products that apply digital technology and include a wide range of products, such as computers, electronic games, TV games, electronic cash registers, switching power supplies, digital clocks, digital watches, calculators, and word processors, and the electromagnetic waves generated by these products are in the frequency band of 200 MHz to 1 GHz.

[0003] In recent years, as electronic devices become smaller and lighter, the electronic devices are becoming more highly integrated and denser, and malfunctions caused by electromagnetic waves are becoming a problem. For this reason, it is required that the housing of the electronic device be given an electromagnetic wave shielding effect in order to shield electromagnetic waves from the outside and to prevent electromagnetic waves from leaking to the outside. To obtain an electromagnetic wave shielding effect, the housing of the electronic device must be conductive, and generally, the higher the conductivity, the better the electromagnetic wave shielding properties. Conventionally, metals have been used for such housings, but attempts have been made to use plastics such as polyarylene sulfide resins from the viewpoint of workability and weight reduction. However, since plastics generally do not have the conductivity of metals, it is necessary to give them conductivity in order to counter electromagnetic interference and electromagnetic noise. Representative methods of giving electromagnetic wave shielding properties to plastics include conductive surface treatments such as plating and methods of incorporating metal powder, metal fibers, carbon fibers, and metal-coated carbon fibers.

[0004] Patent Document 1 discloses a thermoplastic resin composition containing nickel metal-coated carbon fiber using carbon fiber obtained by adjusting O1S / C1S measured by ESCA method on the carbon fiber surface to a specific range. However, this method is not useful for polyarylene sulfide resin, and the electromagnetic wave shielding property is not sufficient. Patent Document 2 discloses a resin composition consisting of polyarylene sulfide resin, modified polyolefin composition, and fibrous filler, but there is no description about thin-wall moldability, and the electromagnetic wave shielding property is not sufficient. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 4674066 [Patent Document 2] JP 2022-114252 A Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a resin composition which is excellent in extrudability, thin-wall moldability and electromagnetic wave shielding properties. [Means for solving the problem]

[0007] Means for Solving the Problems The present inventors have conducted extensive research to achieve the above-mentioned object, and as a result have discovered that by blending metal-coated carbon fiber with at least one resin selected from the group consisting of polyarylene sulfide resin, polyamide resin, and polyester resin, and forming a specific structure, a resin composition having excellent extrudability, thin-wall moldability, and electromagnetic wave shielding properties can be obtained, thereby solving the above-mentioned problems.

[0008] That is, the present invention is as follows. 1. A resin composition comprising 100 parts by weight of a component consisting of 60 to 99.9 parts by weight of (A) polyarylene sulfide resin (component A) and 0.1 to 40 parts by weight of (B) at least one resin selected from the group consisting of polyamide resins and polyester resins (component B), and 5 to 50 parts by weight of (C) metal-coated carbon fiber (component C), wherein, when observed with a scanning electron microscope, resin A of component A forms a matrix, and resin B of component B covers the periphery of metal-coated carbon fiber C of component C. 2. The resin composition according to the above item 1, wherein component A is a polyarylene sulfide resin containing a non-polar functional group at its terminal. 3. The resin composition according to item 2 above, wherein component A is a polyarylene sulfide resin containing a phenyl group at its terminal. 4. The resin composition according to any one of items 1 to 3 above, wherein component B is an aliphatic polyamide. 5. The resin composition according to the above item 4, wherein component B is polyamide 6. 6. The resin composition according to any one of items 1 to 3 above, wherein component B is at least one resin selected from the group consisting of polyethylene terephthalate resin, polyethylene naphthalate resin, polybutylene terephthalate resin, polybutylene naphthalate resin and liquid crystal polyester resin. 7. The resin composition according to any one of the preceding items 1 to 6, wherein the C component is nickel-coated carbon fiber. 8. A molded article obtained by molding the resin composition according to any one of the preceding items 1 to 7.

Effects of the Invention

[0009] Since the resin composition of the present invention is excellent in extrudability, thin-wall moldability, and electromagnetic wave shielding properties, the molded article obtained from the resin composition of the present invention is useful for parts that require electromagnetic wave shielding properties, such as electrical and electronic equipment parts and automobile parts, and the industrial effect achieved is extremely large.

Brief Description of the Drawings

[0010] [Figure 1] It is an observation view of the morphology in the resin composition of Example 1. [Diagram 2] It is an observation view of the morphology in the resin composition of Example 11. [Diagram 3] It is an observation view of the morphology in the resin composition of Comparative Example 1. [Figure 4] It is an observation view of the morphology in the resin composition of Comparative Example 5. [Diagram 5] It is an observation view of the morphology in the resin composition of Comparative Example 8.

Modes for Carrying Out the Invention

[0011] Hereinafter, the details of the present invention will be described.

[0012] <Regarding Component A> A polyarylene sulfide resin is used as Component A of the present invention. The polyarylene sulfide resin may be composed of, for example, a p-phenylene sulfide unit, an m-phenylene sulfide unit, an o-phenylene sulfide unit, a phenylene sulfone unit, a phenylene sulfide ketone unit, a phenylene sulfide ether unit, a diphenylene sulfide unit, a phenylene sulfide unit containing a substituent, a phenylene sulfide unit containing a branched structure, or the like, as its constituent units. Among these, those containing 70 mol % or more, particularly 90 mol % or more of p-phenylene sulfide units are preferred, and poly(p-phenylene sulfide) is more preferred.

[0013] The polyarylene sulfide resin preferably has a polydispersity (Mw / Mn) of 2.7 or more, more preferably 2.8 or more, and even more preferably 2.9 or more, expressed by the weight average molecular weight (Mw) and the number average molecular weight (Mn). If the polydispersity is less than 2.7, there may be a large amount of burrs generated during molding. The upper limit of the polydispersity (Mw / Mn) is not particularly specified, but it is preferably 10 or less. Here, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are values ​​calculated in terms of polystyrene by gel permeation chromatography (GPC). 1-chloronaphthalene was used as the solvent, and the column temperature was set to 210°C.

[0014] The polyarylene sulfide resin is preferably produced by the methods described in U.S. Patent Nos. 4,746,758 and 4,786,713, JP-T-2013-522385, JP-A-2012-233210, and JP-A-5167276.

[0015] The method includes an iodization step and a polymerization step. In the iodization step, an aryl compound is reacted with iodine to obtain a diiodoaryl compound. In the subsequent polymerization step, the diiodoaryl compound is polymerized with solid sulfur using a polymerization terminator to produce a polyarylene sulfide resin. Iodine is generated in gas form in this step, which is recovered and reused in the iodization step. Iodine is essentially a catalyst.

[0016] A representative example of solid sulfur used in the above-mentioned preparation method is cyclooctasulfur (S8) in which eight atoms are bonded at room temperature. However, the sulfur compound used in the polymerization reaction is not limited, and any form that is solid or liquid at room temperature can be used.

[0017] Representative diiodoaryl compounds used in the above-mentioned production method include at least one selected from the group consisting of diiodobenzene, diiodonaphthalene, diiodobiphenyl, diiodobisphenol, and diiodobenzophenone. Also, derivatives of iodoaryl compounds to which an alkyl group or a sulfone group is bonded, or to which oxygen or nitrogen is introduced, are used. Iodoaryl compounds are classified into different isomers depending on the bonding position of the iodine atom, and preferred examples of these isomers are compounds in which iodine is symmetrically located at both ends of the molecule of the aryl compound, such as p-diiodobenzene, 2,6-diiodonaphthalene, and p,p'-diiodobiphenyl. The content of the iodoaryl compound is preferably 500 to 10,000 parts by weight based on 100 parts by weight of the solid sulfur. This amount is determined in consideration of the formation of disulfide bonds.

[0018] In the present invention, it is important that the resin A of the component A forms a matrix, and the resin B of the component B covers the circumference of the metal-coated carbon fiber C of the component C. Although there is no particular limitation on the means for achieving this, it is preferable to use a polyarylene sulfide resin containing a non-polar functional group at the end. Examples of the non-polar functional group include a phenyl group, a vinyl group, an aliphatic hydrocarbon group (alkyl group, cycloalkyl group, etc.), and an aromatic hydrocarbon group (aryl group, arylene group, etc.), and among these, a phenyl group is preferable. By using a polyarylene sulfide resin containing a non-polar functional group at the end, and blending at least one resin selected from the group consisting of polyamide resins and polyester resins and metal-coated carbon fiber, thin-wall moldability and electromagnetic wave shielding properties are improved.

[0019] Typical polymerization terminators used in the above manufacturing method include diphenyl sulfide, diphenyl disulfide, di-2-naphthyl disulfide, bis(2,5-dimethylphenyl) disulfide, etc. Among them, diphenyl sulfide and diphenyl disulfide are preferred. By using these compounds as the polymerization terminator, a polyarylene sulfide resin containing a nonpolar functional group at the terminal can be produced. The content of the polymerization terminator is preferably 1 to 30 parts by weight based on 100 parts by weight of the solid sulfur. This amount is determined in consideration of the formation of disulfide bonds.

[0020] In the above manufacturing method, a polymerization reaction catalyst may be used. Typical polymerization reaction catalysts include nitrobenzene-based catalysts. Preferred examples of nitrobenzene-based catalysts include at least one selected from the group consisting of 1,3-diiodo-4-nitrobenzene, 1-iodo-4-nitrobenzene, 2,6-diiodo-4-nitrophenol, iodonitrobenzene, and 2,6-diiodo-4-nitroamine. The content of the polymerization reaction catalyst is preferably 0.01 to 20 parts by weight based on 100 parts by weight of the solid sulfur. This amount is determined in consideration of the formation of disulfide bonds.

[0021] <Regarding Component B> The resin composition of the present invention contains at least one resin selected from the group consisting of a polyamide resin and a polyester resin as Component B.

[0022] <Polyamide resin> The polyamide resins used as Component B of the present invention include semi-aromatic polyamide resins and aliphatic polyamide resins. One or more of these may be used, and they can be arbitrarily selected according to the purpose.

[0023] The semi-aromatic polyamide resin is composed of an aromatic dicarboxylic acid component and an aliphatic diamine component.

[0024] Examples of the aromatic dicarboxylic acid component include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, and naphthalenedicarboxylic acid, and the dicarboxylic acid component may be one of the above alone or a combination of two or more. As the dicarboxylic acid component, dicarboxylic acids other than aromatic dicarboxylic acids may be used as long as the effects of the present invention are not impaired. Examples of the other dicarboxylic acids include aliphatic dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, and dodecanedioic acid, and alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid.

[0025] Examples of the aliphatic diamine component include 1,2-ethanediamine, 1,3-propanediamine, 1,4-butanediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, 2-methyl-1,5-pentanediamine, and 2-methyl-1,8-octanediamine. These may be used alone or in combination. As the diamine component, diamines other than aliphatic diamines may be used as long as they do not impair the effects of the present invention. Examples of the other diamines include alicyclic diamines such as cyclohexanediamine and aromatic diamines such as xylylenediamine and benzenediamine.

[0026] Examples of aliphatic polyamide resins include poly-ε-capramide (polyamide 6), polytetramethylene adipamide (polyamide 46), polyhexamethylene adipamide (polyamide 66), polyhexamethylene sebacamide (polyamide 610), polyhexamethylene dodecamide (polyamide 612), polyundecamethylene adipamide (polyamide 116), polyundecanamide (polyamide 11), polydodecanamide (polyamide 12), and polyamide copolymers containing at least two different polyamide components among these, or mixtures of these.

[0027] <Polyester resin> Examples of the polyester resin include aliphatic polyester resins, aromatic polyester resins and liquid crystal polyester resins. One or more of these may be used, and they can be arbitrarily selected depending on the purpose.

[0028] Aliphatic polyester resins are made from dicarboxylic acids and diols.

[0029] Examples of the dicarboxylic acid component include 1,3-cyclohexanedicarboxylic acid and 1,4-cyclohexanedicarboxylic acid. One or more of these may be used, and they can be arbitrarily selected depending on the purpose.

[0030] Examples of the diol component include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, neopentyl glycol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, 2,2,4-trimethyl-1,3-pentanediol, and 1,4-cyclohexanedimethanol. One or more of these may be used, and they can be arbitrarily selected depending on the purpose.

[0031] Aliphatic polyester resins include poly(1,3-cyclohexylene dimethylene-1,3-cyclohexane dicarboxylate), poly(1,4-cyclohexylene dimethylene-1,4-cyclohexane dicarboxylate), poly(2,2,4,4-tetramethyl-1,3-cyclobutylene-1,4-cyclohexane dicarboxylate) and copolymers thereof.

[0032] The aromatic polyester resin can be produced using a dicarboxylic acid component mainly composed of a dicarboxylic acid and / or an ester-forming derivative of a dicarboxylic acid, and a glycol component mainly composed of a diol.

[0033] Examples of dicarboxylic acid components include aromatic dicarboxylic acids such as 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, terephthalic acid, isophthalic acid, 4,4'-diphenyldicarboxylic acid, diphenoxyethane-4,4'-dicarboxylic acid, diphenylsulfone-4,4'-dicarboxylic acid, and diphenylether-4,4'-dicarboxylic acid, aliphatic dicarboxylic acids such as adipic acid, sebacic acid, succinic acid, and oxalic acid, and alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid. One or more of these may be used, and can be selected according to the purpose. When two or more dicarboxylic acids are used, the amount of dicarboxylic acid used as the main component is preferably 70 mol% or more, more preferably 80 mol% or more, based on the total acid components. Examples of the ester-forming derivatives of dicarboxylic acids include lower dialkyl esters of aromatic dicarboxylic acids such as 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, terephthalic acid, isophthalic acid, 4,4'-diphenyldicarboxylic acid, diphenoxyethane-4,4'-dicarboxylic acid, diphenylsulfone-4,4'-dicarboxylic acid, and diphenylether-4,4'-dicarboxylic acid; lower dialkyl esters of alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid; and lower dialkyl esters of aliphatic dicarboxylic acids such as adipic acid, sebacic acid, succinic acid, and oxalic acid. One or more of these may be used, and they can be selected arbitrarily depending on the purpose. When two or more dicarboxylic acid ester-forming derivatives are used, the amount of the dicarboxylic acid ester-forming derivative that is the main component is preferably 70 mol% or more, more preferably 80 mol% or more, based on the total dicarboxylic acid ester-forming derivative components. In addition, a small amount of a trifunctional or higher dicarboxylic acid component such as trimellitic acid may be used, and a small amount of an acid anhydride such as trimellitic anhydride may be used. A small amount of a hydroxycarboxylic acid such as lactic acid or glycolic acid or an alkyl ester thereof may also be used, and the acid can be selected arbitrarily depending on the purpose.

[0034] As the glycol component, for example, one or more of alkylene glycols such as ethylene glycol, 1,4-butanediol, 1,3-propylene glycol, 1,2-propylene glycol, neopentylene glycol, hexamethylene glycol, decamethylene glycol, cyclohexanedimethanol, diethylene glycol, triethylene glycol, poly(oxy)ethylene glycol, poly(oxy)tetramethylene glycol, and poly(oxy)methylene glycol may be used, and may be arbitrarily selected depending on the purpose. A small amount of a polyhydric alcohol component such as glycerin may also be used. The amount of the glycol component that is the main component is preferably 70 mol % or more, more preferably 80 mol % or more, based on the total glycol components. The amount of such glycol component is preferably 1.1 mol times or more and 1.4 mol times or less based on the dicarboxylic acid or the ester-forming derivative of the dicarboxylic acid. If the amount of the glycol component is less than 1.1 mol times, the esterification or transesterification reaction may not proceed sufficiently, which is not preferable. Furthermore, if the molar amount exceeds 1.4 times, the reaction rate slows down, although the reason is unclear, and the amount of by-products such as tetrahydrofuran generated from the excess glycol component may increase, which is undesirable.

[0035] In the production of aromatic polyester resin, known polymerization catalysts can be used, such as titanium compounds, antimony compounds, germanium compounds, manganese compounds, aluminum compounds, etc., among which titanium compounds are preferred.Titanium compounds used as polymerization catalysts are preferably tetraalkyl titanates, specifically tetra-n-propyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate, tetra-sec-butyl titanate, tetra-t-butyl titanate, tetra-n-hexyl titanate, tetracyclohexyl titanate, tetraphenyl titanate, tetrabenzyl titanate, etc., and may be used as a mixture of these titanates.Of these titanium compounds, tetra-n-propyl titanate, tetraisopropyl titanate, and tetra-n-butyl titanate are particularly preferred, and tetra-n-butyl titanate is the most preferred. The amount of titanium compound added is preferably 10 ppm or more and 60 ppm or less, more preferably 15 ppm or more and 30 ppm or less, in terms of the titanium atom content in the resulting polyester resin. If the titanium atom content in the resulting polyester resin exceeds 60 ppm, the color tone and thermal stability of the resin composition of the present invention may decrease, which is not preferable. On the other hand, if the titanium atom content is less than 10 ppm, good polymerization activity may not be obtained, and a polyester resin with a sufficiently high intrinsic viscosity may not be obtained, which is not preferable. The polyester resin of the present invention is preferably produced through an esterification or ester exchange reaction process and a subsequent polycondensation reaction process of a dicarboxylic acid component mainly composed of a dicarboxylic acid and / or its ester-forming derivative and a glycol component in the presence of a polymerization catalyst, and the temperature at the end of the esterification or ester exchange reaction is preferably in the range of 180° C. or more and 230° C. or less, more preferably 180° C. or more and 220° C. or less. If the temperature at the end of the esterification reaction or ester exchange reaction exceeds 230° C., the reaction rate increases, but by-products such as tetrahydrofuran may increase, which is not preferable. If the temperature is less than 180°C, the reaction may not proceed.The reaction product (bisglycol ether and / or its oligomer) obtained by the esterification or transesterification reaction is preferably polycondensed at a temperature between the melting point of the polyester resin and 290°C under reduced pressure of 0.4 kPa (3 Torr) or less. If the polycondensation reaction temperature exceeds 290°C, the reaction rate decreases and coloring may become significant, which is not preferable. One or more types of polyester resins may be used, and they can be selected arbitrarily depending on the purpose.

[0036] Representative aromatic polyester resins include, for example, polybutylene naphthalate resin, polyethylene naphthalate resin, polyethylene terephthalate resin, polybutylene terephthalate resin, and copolymers thereof.

[0037] The liquid crystal polyester resin is a thermotropic liquid crystal polyester resin, and has a property that the polymer molecular chains are aligned in a certain direction in a molten state. The form of such an alignment state may be any of nematic, smectic, cholesteric, and discotic forms, and may also have two or more forms. Furthermore, the structure of the liquid crystal polyester resin may be any of main chain, side chain, and rigid main chain bent side chain forms. The form of the alignment state, that is, the nature of the anisotropic molten phase, can be confirmed by a conventional polarized light inspection method using crossed polarizers. More specifically, the confirmation of the anisotropic molten phase can be carried out by observing a molten sample placed on a Leitz hot stage at a magnification of 40 times under a nitrogen atmosphere using a Leitz polarizing microscope.

[0038] The liquid crystal polyester resin preferably contains polyester units and polyesteramide units, and a liquid crystal polyester resin partially containing aromatic polyester units and aromatic polyesteramide units in the same molecular chain is also a preferred example. Particularly preferred is a liquid crystal polyester resin having, as a unit component, one or more compounds derived from aromatic hydroxycarboxylic acids, aromatic hydroxyamines, and aromatic diamines. More specifically, the liquid crystal polyester resins include 1) liquid crystal polyester resins synthesized mainly from one or more compounds selected from the group consisting of aromatic hydroxycarboxylic acids and their derivatives, 2) liquid crystal polyester resins synthesized mainly from a) one or more compounds selected from the group consisting of aromatic hydroxycarboxylic acids and their derivatives, b) one or more compounds selected from the group consisting of aromatic dicarboxylic acids, alicyclic dicarboxylic acids and their derivatives, and c) one or more compounds selected from the group consisting of aromatic diols, alicyclic diols, aliphatic diols and their derivatives, and 3) liquid crystal polyester resins synthesized mainly from a) one or more compounds selected from the group consisting of aromatic hydroxycarboxylic acids and their derivatives, b) one or more compounds selected from the group consisting of aromatic hydroxyamines, aromatic diamines and their derivatives, and c) aromatic dicarboxylic acids. , alicyclic dicarboxylic acid and its derivatives, 4) mainly a) aromatic hydroxycarboxylic acid and its derivatives, b) aromatic hydroxyamine, aromatic diamine and its derivatives, c) aromatic dicarboxylic acid, alicyclic dicarboxylic acid and its derivatives, and d) aromatic diol, alicyclic diol, aliphatic diol and its derivatives, 1) aromatic hydroxycarboxylic acid and its derivatives, alicyclic diol, aliphatic diol and its derivatives, alicyclic polyesteramide resin ...Preferred examples of the specific compounds used in the synthesis of the liquid crystal polyester resin include naphthalene compounds such as 2,6-naphthalenedicarboxylic acid, 2,6-dihydroxynaphthalene, 1,4-dihydroxynaphthalene, and 6-hydroxy-2-naphthoic acid; biphenyl compounds such as 4,4'-diphenyldicarboxylic acid and 4,4'-dihydroxybiphenyl; para-substituted benzene compounds such as p-hydroxybenzoic acid, terephthalic acid, hydroquinone, p-aminophenol, and p-phenylenediamine, and their nuclear-substituted benzene compounds (the substituents are selected from chlorine, bromine, methyl, phenyl, and 1-phenylethyl); and meta-substituted benzene compounds such as isophthalic acid and resorcinol. Among them, p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid are particularly preferred, and a liquid crystal polyester resin formed by mixing the two is suitable. The ratio of the two is preferably in the range of 90 to 50 mol% for the former, more preferably in the range of 80 to 65 mol%, preferably in the range of 10 to 50 mol% for the latter, and more preferably in the range of 20 to 35 mol%.

[0039] The content of component B is 0.1 to 40 parts by weight, preferably 0.5 to 35 parts by weight, and more preferably 1 to 30 parts by weight in 100 parts by weight in total of components A and B. When the content is less than 0.1 part by weight, sufficient electromagnetic wave shielding properties cannot be obtained. When it exceeds 40 parts by weight, the thin-wall moldability deteriorates.

[0040] <Regarding component C> The resin composition of the present invention contains metal-coated carbon fibers as component C. As the carbon fibers used for the metal-coated carbon fibers, any carbon fibers generally referred to as carbon fibers may be used. For example, PAN-based carbon fibers using polyacrylonitrile as a raw material, pitch-based carbon fibers using petroleum tar or petroleum pitch as a raw material, vapor-grown carbon fibers using hydrocarbons or the like as a raw material, and cellulose-based carbon fibers using viscose rayon or the like as a raw material can be mentioned.

[0041] The metal formed on the carbon fiber surface may be silver, copper, iron, nickel, or aluminum, with nickel being preferred from the viewpoint of corrosion resistance of the metal layer. Methods for metal coating include known methods such as plating and vapor deposition, with plating being the most preferred. The thickness of the metal coating layer is preferably 0.1 to 1 μm, more preferably 0.15 to 0.5 μm, and even more preferably 0.2 to 0.35 μm.

[0042] The content of component C is 5 to 50 parts by weight, preferably 8 to 47 parts by weight, and more preferably 10 to 45 parts by weight, relative to 100 parts by weight of the total of components A and B. If the content is less than 5 parts by weight, sufficient electromagnetic wave shielding properties cannot be obtained. On the other hand, if the content exceeds 50 parts by weight, extrudability deteriorates and pelletization becomes difficult.

[0043] <Other ingredients> The resin composition of the present invention can be used in combination with inorganic fillers other than metal-coated carbon fibers, as long as the effects of the present invention are not impaired. Examples of inorganic fillers include fibrous fillers other than metal-coated carbon fibers, powdery fillers, and plate-like fillers. Examples of fibrous fillers include glass fibers, aramid fibers, potassium titanate whiskers, zinc oxide whiskers, alumina fibers, silicon carbide fibers, ceramic fibers, asbestos fibers, gypsum fibers, metal fibers, and inorganic fibers coated with conductive materials other than metals. Specific examples of conductive materials in inorganic fibers coated with conductive materials other than metals include SnO2 (antimony doped) and In2O3 (antimony doped). Examples of inorganic fibers to be coated include glass fibers, potassium titanate whiskers, zinc oxide whiskers, titanic acid whiskers, and silicon carbide whiskers. Examples of coating methods include vacuum deposition, sputtering, electroless plating, and baking. These may be surface-treated with a surface treatment agent such as a titanate-based, aluminum-based, or silane-based coupling agent. In order to obtain better mechanical strength, it is preferable to pretreat these fibrous fillers with a coupling agent such as an isocyanate-based compound, an organic silane-based compound, an organic titanate-based compound, an organic borane-based compound, or an epoxy compound. Examples of powdered fillers include carbon black, calcium carbonate, silica, titanium oxide, graphite, carbon nanotubes, and metal powder, and examples of plate-like fillers include talc and mica.

[0044] The resin composition of the present invention may contain other thermoplastic resins within the range that does not impair the effects of the present invention. Examples of other thermoplastic resins include general-purpose plastics such as polyethylene resins, polypropylene resins, and polyalkyl methacrylate resins, engineering plastics such as polyphenylene ether resins, polyacetal resins, cyclic polyolefin resins, and polyarylate resins (amorphous polyarylate, liquid crystal polyarylate), and so-called super engineering plastics such as polytetrafluoroethylene, polyether ether ketone, polyetherimide, polysulfone, and polyether sulfone.

[0045] The resin composition of the present invention may contain, within the scope of the effect of the present invention, antioxidants and heat resistance stabilizers (hindered phenols, hydroquinones, phosphites, and their substituted derivatives, etc.), weather resistance agents (resorcinols, salicylates, benzotriazoles, benzophenones, hindered amines, etc.), release agents, lubricants (montanic acid and its metal salts, its esters, its half esters, stearyl alcohol, stearamide, various bisamides, bisureas, polyethylene wax, etc.), pigments (cadmium sulfide, phthalocyanine, carbon black, etc.), dyes (nigrosine, etc.), crystal nucleating agents (talc, silica, kaolin, clay, etc.), plasticizers (p-oxygen, etc.), etc.), etc. Other examples of the additives that can be added include: antistatic agents (alkyl sulfate type anionic antistatic agents, quaternary ammonium salt type cationic antistatic agents, nonionic antistatic agents such as polyoxyethylene sorbitan monostearate, betaine type amphoteric antistatic agents, etc.); flame retardants (red phosphorus, phosphate esters, melamine cyanurate, hydroxides such as magnesium hydroxide and aluminum hydroxide, ammonium polyphosphate, brominated polystyrene, brominated polyphenylene ether, brominated polycarbonate, brominated epoxy resins, or combinations of these brominated flame retardants with antimony trioxide, etc.); and other polymers.

[0046] <Method of producing resin composition> The resin composition of the present invention can be produced by mixing the above-mentioned components simultaneously or in any order using a mixer such as a tumbler, a V-type blender, a Nauter mixer, a Banbury mixer, a kneading roll, an extruder, etc. Melt kneading using a twin-screw extruder is preferred, and if necessary, it is preferred to feed any component into the other melt-mixed components from a second feed port using a side feeder or the like.

[0047] The resin extruded as described above is directly cut and pelletized, or strands are formed and then the strands are cut by a pelletizer and pelletized. When it is necessary to reduce the influence of external dust during pelletization, it is preferable to purify the atmosphere around the extruder. The shape of the obtained pellets may be a general shape such as a cylinder, a prism, or a sphere, but is more preferably a cylinder. The diameter of such a cylinder is preferably 1 to 5 mm, more preferably 1.5 to 4 mm, and even more preferably 2 to 3.5 mm. On the other hand, the length of the cylinder is preferably 1 to 30 mm, more preferably 2 to 5 mm, and even more preferably 2.5 to 4 mm.

[0048] <Molded products> Molded articles made of the resin composition of the present invention can be obtained by molding the pellets produced as described above. Preferably, they are obtained by injection molding or extrusion molding. Injection molding includes not only ordinary molding methods, but also injection compression molding, injection press molding, gas-assisted injection molding, foam molding (including a method of injecting a supercritical fluid), insert molding, in-mold coating molding, heat-insulating mold molding, rapid heating and cooling mold molding, two-color molding, multi-color molding, sandwich molding, and ultra-high speed injection molding. Molding can be performed using either the cold runner method or the hot runner method. In addition, extrusion molding can produce various profile extrusion molded products, sheets, films, and the like. Sheets and films can also be molded using the inflation method, calendar method, casting method, and the like. Furthermore, it is possible to mold the resin composition of the present invention into a heat-shrinkable tube by applying a specific stretching operation. It is also possible to mold the resin composition of the present invention into a molded article by rotational molding, blow molding, and the like. Furthermore, the molded articles produced by the above-mentioned various methods can be subjected to various surface treatments. The surface treatment referred to here is a process for forming a new layer on the surface of a resin molded product, such as vapor deposition (physical vapor deposition, chemical vapor deposition, etc.), plating (electroplating, electroless plating, hot-dip plating, etc.), painting, coating, printing, etc., and various methods used for resin molded products can be applied. Furthermore, various types of transport containers and electromagnetic wave shielding covers can be manufactured by subjecting sheet molded products (including ribbon-shaped molded products) to various vacuum forming, heat press forming, bending, etc. EXAMPLES

[0049] The present invention will be described below based on examples. Note that the present invention is not limited to the following examples, and the following examples can be modified or changed based on the spirit of the present invention, and such modifications are not excluded from the scope of the present invention.

[0050] (1) Extrusion property The extrudability during pellet preparation was evaluated as follows. A: Pelletization is possible. ×: Difficult to pelletize.

[0051] (2) Thin-wall formability Using the square plate (size: 150 mm × 150 mm × 1 mm t) obtained by the following method, visual observation was carried out and evaluated as follows. A: Can be formed without problems. B: Low fluidity and cannot be filled sufficiently. C: Peeling occurs in the formed product.

[0052] (3) Morphology Using the square plate (size: 150 mm × 150 mm × 2 mm t) obtained by the following method, the cross-section of the formed product was observed using a scanning electron microscope and evaluated as follows. A: The resin B covers all or part of the periphery of the metal-coated carbon fiber. B: The resin B is in contact with the periphery of the metal-coated carbon fiber but does not cover it or does not cover it without contact.

[0053] (4) Electromagnetic wave shielding characteristics Using the square plate (size: 150 mm × 150 mm × 2 mm t) obtained by the following method, the shielding effects (dB) of the electric field and magnetic field in the region of 100 kHz to 1 GHz were measured using a network analyzer (manufactured by Keysight Technologies) and a KEC method measuring device (manufactured by JSE), and the lowest electric field shielding effect (dB) and magnetic field shielding effect (dB) in the range of 200 MHz to 1 GHz were calculated. In addition, the following materials were used in the examples and comparative examples of the present invention.

[0054] <Component A> A-1: Polyphenylene sulfide resin obtained by the following Production Method 1 [Production Method 1] 300.00 g of paradibenzene and 27.00 g of sulfur were charged with 0.60 g of diphenyldisulfide (content of 0.65 wt% based on the weight of the finally polymerized PPS) as a polymerization terminator, heated to 180 °C to completely melt and mix them, then the temperature was raised to 220 °C and the pressure was reduced to 200 Torr. The obtained mixture was subjected to a polymerization reaction for 8 hours while gradually changing the temperature and pressure so that the final temperature and pressure were 320 °C and 1 Torr, respectively, to obtain a polyphenylene sulfide resin containing a phenyl group at the terminal.

[0055] A-2: Polyphenylene sulfide resin obtained by the following production method 2 [Production method 2] An autoclave equipped with a stirrer was charged with 1814 g of flaky sodium sulfide (Na2S·2.9H2O), 8.7 g of granular caustic soda (100% NaOH: Wako Pure Chemical Industries special grade), and 3232 g of N-methyl-2-pyrrolidone, and the temperature was gradually raised to 200 °C while stirring under a nitrogen stream to distill off 339 g of water. After cooling to 190 °C, 2129 g of p-dichlorobenzene and 1783 g of N-methyl-2-pyrrolidone were added, and the system was sealed under a nitrogen stream. The system was heated to 225 °C over 2 hours, polymerized at 225 °C for 1 hour, then heated to 250 °C over 25 minutes and polymerized at 250 °C for 2 hours. Next, 509 g of distilled water was injected into the system at 250 °C, the temperature was raised to 255 °C, and the polymerization reaction was further carried out for 2 hours. After completion of the polymerization, it was cooled to room temperature, and the polymerization slurry was separated into solid and liquid by a centrifugal filter. The cake was washed successively 3 times with N-methyl-2-pyrrolidone and acetone under a nitrogen stream, and further washed successively with 0.2% hydrochloric acid and warm water under a nitrogen stream. The obtained poly(p-phenylene sulfide) was dried at 105 °C for one day and night to obtain a polyarylene sulfide resin containing no phenyl group at the terminal and containing a thiol group.

[0056] <Component B> B-1: UBE NYLON 1011FB (polyamide 6 manufactured by Ube Industries, Ltd.) B-2: TRN-8550FF (polyethylene terephthalate resin manufactured by Teijin Limited) B-3: TN-8065S (Polyethylene naphthalate resin manufactured by Teijin Limited) B-4: 1200-211D (Polybutylene terephthalate resin manufactured by Changchun Artificial Resin Co., Ltd.) B-5: TQB-OT (Polybutylene naphthalate resin manufactured by Teijin Limited) B-6: UENO LCP A-5000 (Liquid crystal polyester resin manufactured by Ueno Pharmaceutical Co., Ltd.) B-7: UENO LCP A-8100 (Liquid crystal polyester resin manufactured by Ueno Pharmaceutical Co., Ltd.) B-8: ultem 1010 (Polyetherimide resin manufactured by SABIC Japan Co., Ltd.) B-9 (Comparative Example): Panlite L-1225WS (Polycarbonate resin manufactured by Teijin Limited) B-10 (Comparative Example): Lubmer LY1040 (Maleic anhydride-modified ultra-high molecular weight polyethylene manufactured by Mitsui Chemicals, Inc.)

[0057] <Component C> C-1: Tenax-J HT C923 (Fiber diameter: 7.5 μm, cut length: 6 mm, nickel metal-coated carbon fiber manufactured by Teijin Limited)

[0058] (Preparation of test pieces) [Examples 1 to 15, Comparative Examples 1 to 8] The A and B components were fed from the first feed port, and the C component was fed from the second feed port using a side feeder, and pelletized by melt extrusion. Here, the first feed port refers to the feed port at the base, and the second feed port refers to the feed port located between the die and the first feed port of the extruder. The melt extrusion was carried out using a vented twin-screw extruder with a diameter of 30 mmφ equipped with a side screw [TEX30α-38.5BW-3V manufactured by Japan Steel Works, Ltd.]. The extrusion temperatures were C1 / C2 / C3-C11 / D=50°C / 280°C / 300°C / 300°C, the main screw rotation speed was 200 rpm, the side screw rotation speed was 80 rpm, the discharge amount was 20 kg / h, and the vent vacuum degree was 3 kPa. The pellets were dried for 6 hours at 130°C using a hot air circulation dryer, and then an injection molding machine (EC130SXII-4Y, manufactured by Toshiba Machine Engineering Co., Ltd.) was used to produce square plates of 150 mm x 150 mm x 2 mmt and square plates of 150 mm x 150 mm x 1 mmt at a cylinder temperature of 300°C and a mold temperature of 140°C.

[0059] The above-mentioned extrudability, thin-wall formability, and electromagnetic wave shielding properties were evaluated for each of the Examples and Comparative Examples. The results are shown in Tables 1 and 2.

[0060] [Table 1]

[0061] [Table 2]

[0062] <Examples 1 to 15> By blending at least one resin selected from the group consisting of polyarylene sulfide resin, polyamide resin, and polyester resin within the scope of the present invention with metal-coated carbon fiber, the composition exhibited excellent extrudability, thin-wall moldability, a structure in which resin B covers the periphery of the metal-coated carbon fiber, and excellent electromagnetic wave shielding properties with electric field shielding effect and magnetic field shielding effect both exceeding 40 dB. Examples of morphology are shown in Figures 1 and 2.

[0063] <Comparative Example 1> Since it does not contain component B, the metal-coated carbon fiber is not covered with resin B, and the electromagnetic shielding properties are deteriorated. An example of the morphology is shown in Figure 3. <Comparative Example 2> Because the content of component B exceeded the upper limit, thin-wall moldability deteriorated and peeling occurred in the molded product. As a result, it was not possible to obtain a molded product sufficient for measuring the electromagnetic wave shielding properties. <Comparative Example 3> Since it does not contain component C, the electromagnetic wave shielding properties have deteriorated. <Comparative Example 4> Since the content of C component exceeded the upper limit, extrudability was deteriorated and pellets could not be obtained. <Comparative Examples 5 to 7> Since component B is a component different from the claimed range, resin B does not cover the metal-coated carbon fiber, and the electromagnetic shielding properties are deteriorated. An example of the morphology is shown in Figure 4. <Comparative Example 8> Since component A was a component different from the claimed range, resin B did not cover the metal-coated carbon fiber, and the electromagnetic shielding properties were deteriorated. An example of the morphology is shown in Figure 5. [Industrial Applicability]

[0064] The resin composition and molded article of the present invention can be widely used in aviation and railway applications, as well as in various other applications. Since the resin composition of the present invention has excellent extrudability, thin-wall moldability and electromagnetic wave shielding properties, molded articles obtained from the resin composition of the present invention are useful for parts that require electromagnetic wave shielding properties, such as electric and electronic equipment parts and automobile parts, and the industrial effects thereof are extremely large. [Explanation of symbols]

[0065] Resin A of AA component BB component resin B CC component metal coated carbon fiber C

Claims

1. The resin composition contains 5 to 50 parts by weight of (C) metal-coated carbon fiber (component C) per 100 parts by weight of a component consisting of 60 to 99.9 parts by weight of (A) polyarylene sulfide resin (component A) and 0.1 to 40 parts by weight of (B) at least one resin selected from the group consisting of polyamide resins and polyester resins, and is characterized in that, when observed under a scanning electron microscope, resin A of component A forms a matrix, and resin B of component B covers the periphery of metal-coated carbon fiber C of component C.

2. 2. The resin composition according to claim 1, wherein component A is a polyarylene sulfide resin having a non-polar functional group at its terminal.

3. 3. The resin composition according to claim 2, wherein component A is a polyarylene sulfide resin containing a phenyl group at its terminal.

4. 2. The resin composition according to claim 1, wherein component B is an aliphatic polyamide.

5. 5. The resin composition according to claim 4, wherein component B is polyamide 6.

6. 2. The resin composition according to claim 1, wherein component B is at least one resin selected from the group consisting of polyethylene terephthalate resin, polyethylene naphthalate resin, polybutylene terephthalate resin, polybutylene naphthalate resin and liquid crystal polyester resin.

7. 2. The resin composition according to claim 1, wherein component C is nickel-coated carbon fiber.

8. A molded article obtained by molding the resin composition according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Polyarylene sulfide resin composition and method for producing the same

    JP2022114252A

  • Electromagnetic shielding thermoplastic resin composition

    JP4674066B2